Overlap in avian communities produces unimodal richness peaks on Bornean mountains. (21st March 2018) - Burner, Ryan C.; Styring, Alison R.; Boer, Chandradewana; Sheldon, Frederick H.
Abstract: Altitudinal gradients provide tractable, replicated systems in which to study changes in species richness and community composition over relatively short distances. Previously, richness was often assumed to follow a monotonic decline with altitude, but recent meta-analyses show that more complex patterns, including mid-altitude richness peaks, are also prevalent in birds. In this study, we used point counts to survey birds at multiple altitudes on three mountains on the island of Borneo in Sundaland, an area for which quantitative analyses of avian altitudinal distribution are unavailable. In total we conducted 1088 point counts and collected associated habitat data at 527 locations to estimate species richness by altitude on Mt Mulu (2376 m), Mt Pueh (1550 m) and Mt Topap Oso (1450 m). On Mulu, the only mountain with an intact habitat gradient, bird species richness peaks at 600 m. Richness appeared to peak at 600 m on Totap Oso as well, but on Pueh it peaked several hundred metres higher. The richness peak on Mulu differs from that predicted by null models and is instead caused by the overlap of distinct lowland and montane avifaunas, supporting the faunal overlap hypothesis. This finding provides further evidence that a lack of coincidence between peak turnover and peak richness is not sufficient evidence to rule out faunal overlap as a causal factor.